2018
DOI: 10.1590/1983-1447.2017.03.56234
|View full text |Cite
|
Sign up to set email alerts
|

Adesão ao regime terapêutico medicamentoso e aspectos biopsicossociais dos idosos integrados em cuidados continuados domiciliários

Abstract: Adherence to the therapeutic medication and biopsychosocial aspects of elderly integrated in the home-based long-term care Adesão ABSTRACT Objective:To evaluate the association between the biopsychosocial aspects and the adherence to the therapeutic medication of elderly integrated into the home-based long-term care teams. Results: It was observed that 49% of the elderly do not adhere to the therapeutic medication and the level of adherence showed a statistically significant association with nutritional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
4
2
0
7
Order By: Relevance
“…It is known that women tend to seek health services more because they are more compliant with the therapeutic regimen, prevention habits and greater socialization, since they culturally assume responsibility for taking care of themselves and others 9 . The results of this investigation align with those found in a study carried out in Portugal with 451 elderly people from the Algarve region, in which it was observed that 62.1% of the sample was characterized by women 10 .…”
Section: Discussionsupporting
confidence: 90%
“…It is known that women tend to seek health services more because they are more compliant with the therapeutic regimen, prevention habits and greater socialization, since they culturally assume responsibility for taking care of themselves and others 9 . The results of this investigation align with those found in a study carried out in Portugal with 451 elderly people from the Algarve region, in which it was observed that 62.1% of the sample was characterized by women 10 .…”
Section: Discussionsupporting
confidence: 90%
“…The mean number of prescribed drugs taken by the respondents was 3.79. A similar result was found by Monterroso, Joaquim, and Sá (2015) in home care settings, in which a large percentage of individuals (41.8%) took three to five drugs. In the study of Henriques (2011), the participants took a mean of 5.61 prescribed medications on a daily basis.…”
Section: Discussionsupporting
confidence: 83%
“…O perfil de morbidade também é distinto entre gêneros na terceira idade: infarto em homens e predomínio de doenças ósteo-articulares e depressão em mulheres. A depressão esteve associada à baixa adesão em outro estudo, que indicou a possibilidade de que os sintomas depressivos interfiram no estímulo ao autocuidado, causando impacto na adesão ao tratamento farmacológico 12,27 .…”
Section: Discussionunclassified